Molecular Evidence for a Novel Species of Babesia in Unfed Rhipicephalus sanguineus sensu lato (Acari: Ixodidae) - Ozubek, Sezayi; Aktas, Munir (Oxford Univ Press Inc, 2018)
This study reports a novel species of Babesia in unfed Rhipicephalus sanguineus sensu lato and its phylogenetic relationship to other species. One-hundred and forty DNA samples extracted from tick pools comprising 5,403 unfed R. sanguineus s.l. ticks were screened for Babesia. Overall Babesia infection was detected in female, male, and nymph pools with an infection rate maximum likelihood estimate (MLE) of 1.98 (CI 0.65-4.74), 0.50 (CI 0.03-2.40), and 0.07 (CI 0.01-0.21), respectively.Three adult female tick pools (MLE 1.44, CI 0.38-3.88) and one adult male pool (MLE 0.50, CI 0.03-2.40) hybridized to the catchall and Babesia genus probes but did not hybridize to any species-specific probe tested, suggesting the presence of an unidentified Babesia species. Phylogenetic analysis and sequencing revealed the newly detected Babesia isolate to form a Glade distinct from fully identified canine, bovine, equine, and ovine Babesia species, with a range of 88.6-92.9% nucleotide identity.
Keywords: novel Babesia; Babesia ovis; Rhipicephalus sanguineus sensu lato